Implementasi Personal Selling AXA Mandiri Sebagai Alat Komunikasi Pemasaran dalam Memersuasi generasi Z dan Milenial - Dirgantoro, Ganet; Purnamasari , Oktaviana (Jurnal Ilmu Komunikasi, 2025)
Personal Selling is an important part of an insurance company, most of whose products require education for potential consumers. The presence of personal selling is becoming increasingly important considering that the insurance industry is currently not doing well, as seen from data from the Indonesian Life Insurance Association (AAJI), premium holders only grew by 0.5 percent, from 84.40 million to 84.84 million people. Of course, this is interesting to be used as research from a communication science perspective with the object of research being the top insurance company AXA Mandiri related to the strategies applied for personal selling. The purpose of this study is to determine and describe the role of personal selling as a marketing communication tool to persuade potential AXA Mandiri consumers from generation Z and millennials. This study uses the Theory of Reasoned Action (TORA) which explains how attitudes and social norms influence individual behavioral intentions. This model is often used in the context of marketing and consumer behavior to make purchasing decisions. The approach used is descriptive qualitative. Data collection techniques use interviews and observations. Data analysis techniques use the Miles and Huberman concept which consists of data collection, data reduction, and conclusions. From this research, it can be concluded that it is important to understand the behavior of the target audience (millennials and generation Z) in order to educate them to take out insurance.